A "social imbalances procedure" for the EU: Towards operationalisation - Sebastiano Sabato; Bart Vanhercke; Anne-Catherine Guio (European Trade Union Institute (ETUI), 2022)
In view of the formidable challenges ahead related to recovery from the Covid-19 crisis and to the green and digital transitions, the EU social governance toolbox should urgently be strengthened. This paper discusses the conditions for and added value of setting up an EU Social Imbalances Procedure (SIP), which would be a significant step in this direction. It would contribute to ensuring that EU and Member States' policies are organised (more) consistently with the notion of competitive sustainability; it would also contribute to achieving upward social convergence and reducing inequalities. After identifying normative, functional, technical and political arguments that support the creation of a Social Imbalances Procedure, the paper develops two main options for its operationalisation. In the first option, the SIP would cover the whole set of headline indicators currently included in the Social Scoreboard of the European Pillar of Social Rights, while in the second option it would be closely linked to the achievement of the EU social targets agreed upon in 2021. In terms of governance arrangements, the paper envisages a three-stage process: (i) the detection and assessment of social imbalances; (ii) the definition of actions to be taken at the national level (including an EU 'supportive arm'); and (iii) the arrangements to be put in place for monitoring implementation of the Social Imbalances Procedure.
Keywords: 330